Oficina literária de escrita criativa - Siqueira, Yan Patrick Brandemburg (2016)
The Creative Writing became known from Literary Workshops, which have spread since 1970 in Brazil, and currently, through the advent of several sites that share writing techniques. Luiz Antonio de Assis Brasil clarifies that the term "Creative Writing" is used for the writing exercise with creativity domain and that the current literacy, designates the writing of a literary work of any genre, declined a teaching and learning environment , is informal, is academic. Thus, the purpose of a workshop that aims to teach it would be to use specific techniques and motivations in the field of creativity to trigger the writing of literature. In this sense, in addition to discussing concepts of "Literary Workshop" and "Creative Writing" from the studies of different theoretical and workshop instructors interviews, it intends to describe and analyze the functioning of these development practices to writing in Brazil, investigating concepts that manage a literary workshop, its possible methodologies, objectives and scope, and thus seeking to reduce what it considers a shortfall in the number of studies in Creative Writing area.